PERBANDINGAN KUALITAS HIDUP, TINGKAT KECEMASAN, DAN KEMAMPUAN ACTIVITY DAILY LIVING PADA PASIEN DEWASA DAN LANSIA DENGAN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA - Regita Siti Nurjanah (2022)
Chronic kidney failure is disorder kidney function where body is unable to excrete waste, marked by glomerular filtration rate < 15 mL/min/1.73 m2 in 3 months. This disease generally affects elderly patients, but it's possible adult patients can get this disease. Disease affects quality of life, anxiety, and daily activities become hampered. Aim is see differences quality of life, anxiety, and ability to activity daily living in adult and elderly patients with chronic kidney failure undergoing hemodialysis. Instrument used questionnaire, namely World Health Organization Quality of Life-Bref, Zung Self-rating Anxiety Scale and Barthel Index. Sampling technique using Non Probability Sampling amounted to 86 respondents. This study, Cross Sectional approach was used with T-Independent test analysis. Result is there are differences quality of life adult and elderly patients with chronic kidney failure with hemodialysis, namely physical health domain P-Value 0.017, psychological domain P-Value 0.030 and social support domain P-Value 0.025. Total overall quality of life domain adult patients is higher than elderly. Results anxiety adult and elderly patients are P-Value 0.019, meaning elderly patients have lower anxiety than adults. As for daily living activity, result is P-Value of 0.011, meaning elderly tend to have lower daily living activities compared to adults.